Assessing AI-driven dubbing websites: Reactions of Arabic native speakers to AI-dubbed English videos in Arabic - Ahmad, Maysa; Haider, Ahmad S; Saed, Hadeel (Research Journal in Advanced Humanities, 2025)
In the era of rapid Artificial Intelligence (AI) advancements, emerging tools have become essential components of our daily routine. AI-dubbing aims to speed up localisation by replacing the original soundtrack with AI-generated sounds. These developments raise the question of whether human dubbers could be replaced in the future. This study quantitatively examines viewers’ reactions to the AI Arabic-dubbed versions of the “Pride and Prejudice” movie using AI dubbing tools from two websites: ElevenLabs and Dübverse. The participants are asked to watch the original video along with two dubbed videos generated by the two websites. For data collection purposes, a three-point Likert scale questionnaire consisting of 19 items and five constructs —linguistic issues, technical issues, synchronisation, translation quality, and attitudes and future recommendations —was designed to elicit the reactions of 150 native Arabic speakers. The analysis shows that linguistic issues, technical issues, synchronisation, and translation quality significantly affected the participants’ attitudes and future recommendations regarding the use of AI-dubbing services. 80% of the respondents acknowledged that AI-dubbing is beneficial for making content accessible to a wider audience. The study found that ElevenLabs outperforms Dübverse, especially in areas such as voice cloning, maintaining both kinesic and isochrony, handling colloquial language, managing multiple speakers, and achieving overall better performance in translation. The findings showed that both websites lack lip-synchrony and require enhancements in other areas. This study is beneficial for content creators seeking to expand their reach globally. The study recommends conducting further research on AI-dubbing across different genres and languages.